Patterns of Student Thinking Interaction in Group Discussion: The Effect of Explorative Interaction on Understanding Statistical Concepts - Syarifudin, Syarifudin; Haris, Abd.; Nurrahmah, Nurrahmah (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
This study aims to analyze patterns of students' thinking interaction during group discussions in statistics learning and examine their impact on conceptual understanding, particularly across different levels of academic ability. A qualitative approach was employed using discourse and interaction analysis. Data were collected through classroom observations, video/audio recordings, transcription of student discussions, students' written work, and in-depth interviews. These instruments enabled comprehensive documentation and triangulation of students' verbal and behavioral interactions. Twelve junior high school students were selected and categorized into high, medium, and low academic ability groups. Discourse structures were analyzed using the Sinclair & Coulthard model (to identify classroom discourse moves) and Mercer's framework (to detect exploratory and cumulative talk). Furthermore, interaction patterns were categorized using the ICAP model—which distinguishes passive, active, constructive, and interactive engagement—and Bales’ Interaction Process Analysis (IPA), which classifies social-emotional and task-related behaviors in small groups. The findings revealed that groups with explorative interaction patterns demonstrated deeper conceptual understanding, facilitated by active questioning, argument construction, and peer clarification. In contrast, static interaction groups were characterized by passive reception and rote learning, while counterproductive groups showed fragmented participation and communication breakdowns. These results confirm the vital role of interaction quality in supporting conceptual development. The novelty of this study lies in its integration of discourse- and interaction-based frameworks to reveal how different thinking dynamics shape learning outcomes in heterogeneous academic groups. Practically, the study highlights the importance of scaffolding, open-ended questioning, and structured facilitation to promote argumentation-rich discussions. These strategies are essential for fostering critical thinking and improving students’ understanding of statistics concepts.